2016
DOI: 10.1117/1.jmi.3.2.023501
|View full text |Cite
|
Sign up to set email alerts
|

High spatial resolution diffusion weighted imaging on clinical 3 T MRI scanners using multislab spiral acquisitions

Abstract: , "High spatial resolution diffusion weighted imaging on clinical 3 T MRI scanners using multislab spiral acquisitions," J. Med. Imag. 3(2), 023501 (2016) Abstract. A diffusion weighted imaging (DWI) approach that is signal-to-noise ratio (SNR) efficient and can be applied to achieve sub-mm resolutions on clinical 3 T systems was developed. The sequence combined a multislab, multishot pulsed gradient spin echo diffusion scheme with spiral readouts for imaging data and navigators. Long data readouts were used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…High-resolution DTI data were acquired using a 3-D multi-slab, multishot spiral sequence designed to achieve high spatial resolution through optimized signal-to-noise efficiency and reduced distortion artifacts (Holtrop & Sutton, 2016;Johnson et al, 2014). Imaging parameters included 30 encoding directions at b value = 1000 sec/mm 2 , 2 encodings at b value = 0 sec/mm 2 , repetition time/echo time = 1875/82 msec, field of view = 240 × 240 mm 2 , matrix = 150 × 150, 2 in-plane spiral shots (parallel imaging R = 2); 15 slabs with 4 slices per slab.…”
Section: Dti Acquisition and Processingmentioning
confidence: 99%
“…High-resolution DTI data were acquired using a 3-D multi-slab, multishot spiral sequence designed to achieve high spatial resolution through optimized signal-to-noise efficiency and reduced distortion artifacts (Holtrop & Sutton, 2016;Johnson et al, 2014). Imaging parameters included 30 encoding directions at b value = 1000 sec/mm 2 , 2 encodings at b value = 0 sec/mm 2 , repetition time/echo time = 1875/82 msec, field of view = 240 × 240 mm 2 , matrix = 150 × 150, 2 in-plane spiral shots (parallel imaging R = 2); 15 slabs with 4 slices per slab.…”
Section: Dti Acquisition and Processingmentioning
confidence: 99%
“…A major hurdle in performing submillimeter isotropic resolution dMRI is its inherently low signal-to-noise (SNR). Recently, simultaneous multislice (SMS) (6)(7)(8)(9)(10)(11) and 3D multislab (12)(13)(14)(15) acquisitions have been developed to improve dMRI's SNR efficiency. Conventional slice-by-slice dMRI exhibits long repetition times (TRs) as a result of the lengthy diffusion encoding that is repeated for each imaging slice.…”
Section: Introductionmentioning
confidence: 99%
“…6 Inference across the candidate acquisition options demonstrated that a single low to medium b-value was sufficient for second fiber detection only, but that low b-value in combination with high b-values was necessary to resolve threeway crossings; in such a multishell (ie, multi b-value) diffusion encoding, the difference between shells had to be larger than 750 s/mm 2 to significantly aid in third fiber detection. These guidelines and experimental evaluations performed with pilot data supported a proposed three-shell acquisition in the young-adult WU-Minn HCP with b = 1000, 2000, 3000 s/mm 2 and Δb = 1000 s/mm 26 ; because of the shorter total scan times needed in the Lifespan HCP, the dMRI FIGURE 8: Sensitivity of different q-space sampling schemes in resolving (two-and three-way) crossing fibers within the centrum semiovale. The amount of crossings resolved by each scheme is normalized by the maximum.…”
Section: Q-space Samplingmentioning
confidence: 74%
“…The HCP Lifespan, where the dMRI resolution is 1.5 mm isotropic and 4-fold slice acceleration is employed, achieves a shorter TR (3200 msec) (Table 1), 12 which is still longer than the optimal TR. Thus, TR and volume acquisition times (VAT), 1 which are the same in a slice-based imaging approach, are suboptimal in the HCP; reducing this parameter towards the optimal value requires both reducing TE and increasing image accelerations, irrespective of the imaging approach used, whether slice-based as in the HCP or segmented 3D EPI or spiral trajectory acquisitions (eg, 20,[24][25][26] ) that are gradually being explored as an alternative. This in turn requires major new developments in hardware as well as image acquisition and reconstruction strategies, which are increasingly a major focus of the post-HCP era in the development of dMRI as well as fMRI techniques.…”
Section: Se-epi Signal Magnitude and Snr Efficiencymentioning
confidence: 99%